THE EFFECT OF NUMBERED HEADS TOGETHER TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN READING RECOUNT TEXT - Freddy Simarmata; Masitowarni Siregar (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2017)
The objective of this study was to investigate whether Numbered Heads Together Technique significantly affected on students’ achievement in reading recount text. This study was an experimental research design. The population of this study was grade X students of SMA Swasta Teladan Medan with the total number of students was 60 as samples and all of the students was taken by using random sampling. The students were divided into two groups, namely experimental and control group. The experimental group was taught by using Numbered Heads Together Technique, while the control group was taught by using Lecturing Method. The instrument of collecting data was multiple choice tests which then divided into pre-test and post-test. To obtain the result of the reliability of the test, the researcher used the Kuder Richardson formula (KR-21). The result of the calculation showed that the reliability of the test was 0.64, which means that the reliability of the test is high. The data were analyzed by using t-test formula. The result of the analysis showed that tvalue is higher than ttable (5.50 > 2.00) at the level of significance 0.05 with the degree of freedom (df) 58. It means that there is a significant effect of using Numbered Heads Together Technique on the students’ achievement in reading recount text.   Keyword: Numbered Heads Together Technique, Reading Achievement.